Chemical composition of the essential oil of Asarum glabrum Merr. in Vietnam - Thai, Tran Huy; Hien, Nguyen Thi; Minh, Do Thi; Tuan, Nguyen Anh (Academia Journal of Biology, 2012)
Asarum glabrum (Aristolochiaceae) distributes in many provinces of Vietnam such as Ha Giang, Lai Chau, Lao Cai, Tuyen Quang, Vinh Phuc and Hanoi. This species is listed as vulnerable in the Red Data Book of Vietnam (1996, 2007) and in the Governmental Decree 32/2006/NĐ/CP. Up to now, there has been no research on Asarum spp. in Vietnam. The essential oil from aerial parts of the plant was obtained by steam distillation and yielded 0.36% by air dry material. This essential oil was analysed by GC/MS and 31 constituents were identified. The major constituents found in the oil were safrol (42.24%), apiole (27.11%) and myristicin (6.13%).